The Potential of Srigading Plants (Nyctanthes arbor-tristis) as Aedes aegypti Larvicides - Fakhriadi, Rudi; Rosadi, Dian; H. D. Lasari, Hadrianti; Mustawan, Elwan; Maulidah, Siti (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2023)
Dengue Hemorrhagic Fever (DHF) is an endemic disease that causes high morbidity and mortality rates. The prevalence of DHF in Indonesia (2018) reached 24.75 per 100,000, and in South Kalimantan (2019) was 56.83 per 100,000 population. One of the efforts to control dengue vectors is the use of larvicides. The purpose of this study was to determine the potential of Srigading Plants (Nyctanthes arbor-tristis) as Aedes aegypti larvae as vectors of DHF in Wetlands. This study used a true experimental research design using the post-test-only controlled group design to determine the effectiveness of Srigading extract (Nyctanthes arbor-tristis) against the death of Aedes aegypti instar IV mosquito larvae. Based on the results, a significance value or p-value of 0.0001 0.05 was obtained. It indicated a significant difference between the number of mosquito larvae deaths and the concentration of Srigading extract given.